Parenting Styles and EFL Motivation: A Phenomenological Study in Indonesian Vocational Education - Julianti; Maulina; Sain, Yuliyanah; Hermansyah, Sam; Narciso, Sheryl Ann V. (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates how parenting styles shape students’ motivation to learn English in an Indonesian vocational high school. Adopting a qualitative phenomenological approach, the study involved seven students, seven parents, and two English teachers. Data were gathered through semi-structured interviews, classroom observations, and field notes, and analyzed using thematic analysis. The findings indicate that students’ motivation was dynamic and context-dependent, with stronger engagement at school than at home. In the classroom, motivation was reflected in active participation, peer interaction, persistence, and future-oriented goals. At home, motivation tended to weaken because of limited parental monitoring and the lack of structured learning routines. Although parents provided little direct academic supervision, they influenced motivation indirectly through reminders, encouragement, recognition of effort, and support for study time and space. These practices supported students’ needs for autonomy, competence, and relatedness. In addition, teacher support, classroom climate, peer interaction, and future aspirations played a compensatory role when home support was limited. The study contributes to the EFL motivation literature by showing that motivation is both psychologically experienced and behaviorally observable, emerging through the interaction of family practices, school environment, and personal goals.